Effect of Pollen Grains and Growth Regulator NAA on Some Fruit Characterization of Date Palm Phoenix dactylifera L Cultivar. Sultani - Hader Abdalkhadhm Hamzah; Imad Ali Aubied (Al-Qadisiyah Journal For Agriculture Sciences, 2019)
This research was conducted in orchard belong to Al-Mahawel date palm station (Abo Sderah) / Ministry of Agriculture located in governorate of Babylon, during the season 2015-2016. Twenty four uniform date palm Phoenix dactylifera. L. Sultani cultivar were used , to study the effect of the pollinator type (P1: Ghannamiakhder , P2: Ghannamiahmer and P3:khukri ), the concentration of Naphthalene Acetic Acid NAA(0 , 50 and 100 ) mg.L-1 and their interaction on fruits setting up , fruits drop and some of physical and chemical characteristics of fruits of date palm Sultani cultivar .Experiment carried out as factorial experiment(3×3) by Randomized Complete Block Design (RCBD) with three replications in each treatment , and the means were compared using LSD level of significant test at P ≤ 0·05. The results can be summarized as that Ghannamiahmer (P2) cultivar and 50 mg.L-1 NAA application showed a significant increase in the fruit setting% , while Khukri cultivar(P3) showed significantly increased fruit size and weight as compared with the other cultivars.Furthermore the cultivar(P1) obtained a significant increase in the bunch weight in Rutab stage as compared with the other cultivars. While the cultivar(P2)with 100 mg.L-1 NAA application showed significant increase in bunch weight in Rutab stage as compared with the other interactions. Ghannamiakhder (P1) cultivar had a significant increase in the fruit content of reducing sugars and non-reducing sugars, while khukri showed significant increase in fruit content of dry matter% and total sugars as compared with the other cultivars..